PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA DALAM PELAJARAN SENI BUDAYA (SENI RUPA) KELAS XI DI MAN 3 KOTA PADANG - WAHYU RAHMADANI, Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of the study was to find out the differences in learning outcomes of Project Based Learning and Conventional learning learning models in the learning of Cultural Arts (Fine Arts) class XI MAN 3 in Padang City. in accordance with the background, the form of this research is an experiment, through a research design pretest-postest control group design. The population of this study is students of class XI MAN 3 in Padang City. local What was chosen as the research object was the class XI IPS1 experimental class and class XI IPS2 control class, sample selection using random sampling. based on hypothesis testing carried out that knowncalculations, t count = 5.736 and t table = 1.999, this shows that t count> t table, it can be concluded Ha is accepted. It can be concluded the learning ability in fine arts subjects with the PjBL learning model. significantly different from students' learning abilities in learning art which with conventional strategies in class XI MAN 3 Kota Padang. this is a positive result for improving students' learning abilities in class XI MAN 3 subjects in the city of Padang.Keywords: results of learning ability, Projeck based learning model, conventional learning model